Ethical Governance Experience of Medical Big Data Research in the UK and Its Implication: Take the University of Leicester as An Example - Xuechao WU; Jing CHAO (Yixue yu zhexue)
To address the ethical challenges of medical big data research, University of Leicester proposes a dual-governance scheme of legal regulation and value balance to survive the potential ethics crisis in the UK-REACH project. On one hand, it common law confidentiality, data protection laws, and human rights legislation to regulate the ethical aspects of its medical big data research. On the other hand, it pursues substantive and procedural value governance to balance competing interests, such as personal privacy, research data protection, social justice, and the public interest. The ethical governance of the UK-REACH project adequately reflects the multiple ethical values balance and the ecological complementarity between legal regulation and value governance of big data medical research in the age of open science.